Environmental health risk analysis of exposure to airborne particulate matter (PM10 and PM2.5) in residential areas surrounding a nickel smelter - Sukmawati Sukmawati; Fais Satrianegara; Muh. Saleh; Andi Susilawaty; Irham Irham (Institute of Accounting Research and Novation (IARN), 2026)
Comunities surrounding nickel smelters may be exposed to particulate emissions, yet evidence from Indonesia remains limited, particularly studies integrating measured PM₁₀ and PM₂.₅ concentrations with individual exposure characteristics. This study estimated non-carcinogenic inhalation risks among residents of Borongloe Village, which was selected because its settlements are located close to a nickel smelter industrial area in Bantaeng Regency. A descriptive study using Environmental Health Risk Assessment (EHRA) included 40 adult residents, with 10 representing the area surrounding each of four sampling points. Ambient concentrations were measured gravimetrically using a high-volume air sampler. EHRA integrated the measured concentrations with individual exposure time, frequency, duration, and body weight to estimate inhalation intake and risk quotients (RQs). Mean concentrations were 30.65 µg/m³ for PM₁₀ and 11.57 µg/m³ for PM₂.₅. The corresponding mean RQs were 0.0546 and 0.0287, while the maximum RQs were 0.2035 and 0.1169. All RQs were below one, although residents exposed for more than four hours per day had the highest estimates. Because measurements lasted only 90–120 minutes and the smelter was not operating at full capacity, these values indicate no appreciable non-carcinogenic risk only under the observed exposure scenario and do not demonstrate long-term safety. The results provide a practical basis for prioritizing air-quality monitoring, emission control, risk communication, and protection of residents with longer outdoor exposure. By integrating environmental measurements with individual exposure parameters, this study provides a site-specific baseline EHRA for an understudied community near an Indonesian nickel smelter. Repeated 24-hour and long-term monitoring during normal operations is required to determine risks under representative operating conditions.